Center for Socio-Legal Research and Extension of the Faculty of Law and Social Sciences - Ariza Barbosa, Nilce (Universidad Pedagógica y Tecnológica de Colombia, 2003)
The Socio-Legal Research and Extension Center is created with a projection or vision towards the construction of a School of Legal Thought. The creation of a research culture is a possible process based on the creative spirit and commitment of the Educational Community: teachers, students, administration and the local and regional community, where it is understood that Integral Training towards a School of Socio-Legal knowledge creation